On the daddy long-legs spiders of the genus Physocyclus (Araneae: Pholcidae) from Mexico: description of a new species from the Baja California Peninsula - Samuel Nolasco; Alejandro Valdez-Mondragón (Revista Mexicana de Biodiversidad)
A new species of daddy long-legs spiders of the genus Physocyclus Simon, 1893 of the globosus species group is described from the Baja California Peninsula desert, in the state of Baja California Sur, Mexico. The species is described based on adult males and females: Physocyclus xerophilus sp. nov. This is the sixth species described from Baja California Sur. The total number of species of Physocyclus increases to 34, including the new species described herein. Thirty-two of 34 species are distributed in Mexico, with one cosmopolitan: Physocyclus globosus. The states of Baja California Sur, Guerrero and Michoacán have the highest diversity of species in the country, with 8 species each.